A global topology map of the Saccharomyces cerevisiae membrane proteome - Kim, Hyun (National Academy of Sciences, 2006)
The yeast Saccharomyces cerevisiae is, arguably, the best understood eukaryotic model organism, yet comparatively little is known about its membrane proteome. Here, we report the cloning and expression of 617 S. cerevisiae membrane proteins as fusions to a C-terminal topology reporter and present experimentally constrained topology models for 546 proteins. By homology, the experimental topology information can be extended to ≈15,000 membrane proteins from 38 fully sequenced eukaryotic genomes.